The Effect of Group Guidance Services with Problem Solving Techniques to Improve Self-Regulation in Students - Fanany, Jida Alfian; Ismanto, Heri Saptadi; Ismah, Ismah (An-Nadwah, 2024)
Self-regulation is one very important aspect for students. From the results of the analysis shows that self-regulation in students is still lacking. This study aims to determine the effect of group guidance services with problem solving techniques to improve self-regulation in students represented by SMP NEGERI 5 Jepara class IX students. The method used in this research is quantitative research with the type of true experimental with the pretestposttest control group design model, using a questionnaire with a Likert scale . The initial condition regarding self-regulation is known as 10% in the very low category, 80% of students in the low category, and 10% in the high category for the experimental group. The control group got a low category with a presentation of 90% and a high category with a percentage of 10%. After being given group guidance services with problem solving techniques . Student self-regulation increased to 20% very high category and high category with a percentage of 80%. Meanwhile, the control class got a low category with a presentation of 90% and a high category with a percentage of 10%. The results showed that group guidance services with problem solving techniques can influence and improve student self-regulation. It can be concluded that there is a significant influence on the self-regulation of students of SMP Negeri 5 Jepara class IX before and after group guidance services with problem solving techniques.